Extraction and purification of purple membrane for photochromic thin film development: Application in photoelectrochemical investigation - Pandey P.C.; Pandey D.; Singh R. (My University, 2025)
Purple membrane (PM) has been extracted and purified from archaebacteria for thin film development. The purified purple membrane is isolated in 1% polyvinyl alcohol solution for making thin film within gelatin and organically modified silicate matrices. For thin film within gelatin matrix, homogenized purple membrane suspension is mixed with 8% gelatin and poured into a specially designed block with desired thickness of spacer having hydrophobicity followed by gelatinization of the same over home-made thermostatic control unit at 38 °C. The gelatinized matrix is then allowed to dry under controlled conditions of humidity and temperature. The films of varying thicknesses ranging between 40, 50, and 60 μ are used for photo-electrochemical measurements. The results on photoelectrochemistry of non-oriented purple membrane film provides valuable information on the generation of forward (light on) and backward (light off) photocurrent as a function of: (a) applied potential and (b) film thickness. An increase in applied negative potential increases the amplitude of photocurrent whereas decrease in film thickness facilitates the reversibility of photocurrent response. © Springer Science+Business Media, LLC 2012.